The Trends in Global Gene Expression in Mouse Embryonic Stem Cells During Spaceflight - An, Lili; Li, Yanming; Fan, Yingjun; He, Ning; Ran, Fanlei; Qu, Hongzhu; Wang, Yanqiu; Zhao, Xuetong; Ye, Chen; Jiang, Yuanda; Fang, Xiangdong; Hang, Haiying (Frontiers in Genetics, 2019)
The environment in space differs greatly from the environment on the ground. Spaceflight causes a number of physiological changes in astronauts, such as bone loss and immune system dysregulation. These effects threaten astronauts' space missions, and understanding the underlying cellular and molecular mechanisms is important to manage the risks of space missions. The biological effects of spaceflight on mammalian cells, especially with regards to DNA damage, have attracted much attention. Rad9-/- mouse embryonic stem cells (mESCs) are known to be extremely sensitive to DNA damage agents. In this study, a project of the SJ-10 satellite programme, we investigated the gene expression profiles of both Rad9-/- mESCs and Rad9+/+ (wild-type) mESCs in space with a focus on genes critical for inducing, preventing or repairing genomic DNA lesions. We found that spaceflight downregulated more genes than it upregulated in both wild-type and Rad9-/- mESCs, indicating a suppressive effect of spaceflight on global gene expression. In contrast, Rad9 deletion upregulated more genes than it downregulated. Of note, spaceflight mainly affected organ development and influenced a wide range of cellular functions in mESCs, while Rad9 deletion mainly affected the development and function of the haematological system, especially the development, differentiation and function of immune cells. The patterns of gene expression in mouse embryonic stem cells in space is distinct from those in other types of cells. In addition, both spaceflight and Rad9 deletion downregulated DNA repair genes, suggesting a possibility that spaceflight has negative effects on genome for embryonic stem cells and the effects are likely worsen when the genome maintenance mechanism is defective.